A Study of the Protective Effect of Bushen Huoxue Prescription on Cerebral Microvascular Endothelia Based on Proteomics and Bioinformatics. (6th January 2022) - Zhao, Shao-Yang; Zhao, Huan-Huan; Li, Yi-Ming; Wang, Bao-Hua; Li, Sai-Mei
Abstract : Diabetic cognitive dysfunction is a serious complication of type 2 diabetes mellitus (T2DM), which can cause neurological and microvascular damage in the brain. At present, there is no effective treatment for this complication. Bushen Huoxue prescription (BSHX) is a newly formulated compound Chinese medicine containing 7 components. Previous research indicated that BSHX was neuroprotective against advanced glycosylation end product (AGE)-induced PC12 cell insult; however, the effect of BSHX on AGE-induced cerebral microvascular endothelia injury has not been studied. In the current research, we investigated the protective effects of BSHX on AGE-induced injury in bEnd.3 cells. Our findings revealed that BSHX could effectively protect bEnd.3 cells from apoptosis. Moreover, we analyzed the network regulation effect of BSHX on AGE-induced bEnd.3 cells injury at the proteomic level. The LC-MS/MS-based shotgun proteomics analysis showed BSHX negatively regulated multiple AGE-elicited proteins. Bioinformatics analysis revealed these differential proteins were involved in multiple processes, such as Foxo signaling pathway. Further molecular biology analysis confirmed that BSHX could downregulate the expression of FoxO1/3 protein and inhibit its nuclear transfer and inhibit the expression of downstream apoptotic protein Bim and the activation of caspase, so as to play a protective role in AGE-induced bEnd.3 injury. Taken together, these findings demonstrated the role of BSHX in the management of diabetic cerebral microangiopathy and provide some insights into the proteomics-guided pharmacological mechanism study of traditional Chinese Medicine.